2007
DOI: 10.1152/japplphysiol.00315.2007
|View full text |Cite
|
Sign up to set email alerts
|

Changes in sleep quality of athletes under normobaric hypoxia equivalent to 2,000-m altitude: a polysomnographic study

Abstract: This study evaluated the sleep quality of athletes in normobaric hypoxia at a simulated altitude of 2,000 m. Eight male athletes slept in normoxic condition (NC) and hypoxic conditions equivalent to those at 2,000-m altitude (HC). Polysomnographic recordings of sleep included the electroencephalogram (EEG), electrooculogram, chin surface electromyogram, and electrocardiogram. Thoracic and abdominal motion, nasal and oral airflow, and arterial blood oxygen saturation (Sa(O(2))) were also recorded. Standard visu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
2
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 37 publications
4
42
2
1
Order By: Relevance
“…Thus, PSG has long been used to examine sleep quality changes across development and aging, after drug administration, and in pathological conditions and circumstances. [1][2][3][4] Since 1968, methods for PSG sleep evaluation have been standardized [5][6][7] making it possible to compare a generation of studies recorded in geographically and chronologically varied environments. Thus, for example, Kobayashi et al 8 were recently able to conduct a meta-analysis of 20 PSG studies to compare sleep in people with and without post-traumatic stress disorder (PTSD), finding PTSD patients had more stage 1 sleep, less slow-wave sleep, and greater rapid-eye-movement density.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, PSG has long been used to examine sleep quality changes across development and aging, after drug administration, and in pathological conditions and circumstances. [1][2][3][4] Since 1968, methods for PSG sleep evaluation have been standardized [5][6][7] making it possible to compare a generation of studies recorded in geographically and chronologically varied environments. Thus, for example, Kobayashi et al 8 were recently able to conduct a meta-analysis of 20 PSG studies to compare sleep in people with and without post-traumatic stress disorder (PTSD), finding PTSD patients had more stage 1 sleep, less slow-wave sleep, and greater rapid-eye-movement density.…”
Section: Introductionmentioning
confidence: 99%
“…However, in our previous study we demonstrated significant decreases in both visually scored slow-wave sleep and the underlying whole-night delta power of NREM sleep EEG at a simulated altitude of 2000 m (Hoshikawa et al, 2007). In that study, the subjects revealed lower mean blood oxygen saturation (SpO 2 ) than subjects in previous studies.…”
Section: Introductionmentioning
confidence: 65%
“…Polysomnography in 8 male athletes acclimatized at sea level, when first sleeping at simulated 2000-m altitude, showed less slow-wave sleep (stages 3 and 4) and total delta power (Ͻ3 Hz) of the all-night NREM sleep, and significantly reduced Sp O 2 , but neither subjective subsequent sleepiness nor altered urinary catecholamines (Hoshikawa et al, 2007).…”
Section: Unacclimatized Athletes Show Mild Sleep Disturbances At 2000mentioning
confidence: 88%